IMPROVING JUNIOR HIGH SCHOOL STUDENTS’ ENGLISH VOCABULARY THROUGH learnenglish.de WEBSITE - Bintang, Istri Rosiana; Ikhwanul Fattah, Mukhammad Aydin; Fajrin, Nazwa; Khomarudin, Khomarudin (LINGUAMEDIA Journal, 2024)
Students who enter junior high school must have master the basics of the international language, that is English language, so that when entering senior high school students are proficient in English. The purpose of this study is to find out whether the learnenglish.de website is able to influence students' skills in English, especially in mastering English vocabulary. This type of research was included in the type of qualitative research with a descriptive study approach. This research was conducted specifically, detail, and in depth with students. The results of this study include; Many students were helped by online courses, moreover free courses, in improving English skills. In addition, 86,4% of 44 students agreed that the learnenglish.de website was worth using to improve their English skills, especially in terms of vocabulary. This was proven by the existence of various types of learning related to English in the website. Keywords: English vocabulary; learnenglish.de website; Junior high school students; learn English; English skills